Strongyloides Colitis: Gastrointestinal Manifestation of Helminthiasis Resemble Inflammatory Bowel Disease - Winni Aprillia Putri; Annisa Zahra Mufida; Titong Sugihartono (Institute of Topical Disease Universitas Airlangga, 2026)
Strongyloides stercoralis is an intestinal parasitic nematode classified as a Soil-Transmitted Helminth (STH) and estimated to infect up to 100 million people worldwide. The prevalence of STH is higher in tropical developing countries, such as Indonesia. This disease can manifest as a digestive tract infection, and in a few cases, also as colitis. Strongyloides colitis frequently exhibits clinical and endoscopic features that closely resemble those of Inflammatory Bowel Disease (IBD), particularly Ulcerative Colitis (UC). Their resemblance could lead to diagnostic errors and also mistreatment. Here we present a case of helminthiasis manifested as Strongyloides colitis in an at-risk elderly person from an endemic area. This study aims to highlight the complex diagnostic and treatment challenges to achieve a better prognostic outcome. A 61-year-old female was referred with a history of prolonged diarrhea accompanied by worsening abdominal pain. The colonoscopy demonstrated features of helminth colitis. A single dose of an anthelmintic was administered, after which the patient showed progressive improvement within two weeks. Six months of follow-up after treatment showed satisfactory results. In typical symptoms of colitis, detection of the underlying cause is very important. This uncommon case report is intended as an alert to avoid further misdiagnosis of helminth colitis from UC, since the cure rate is relatively high with appropriate medication. Further discussions on initial diagnostic tools and comprehensive treatment are needed, along with integration into global helminth control strategies.